Ellagitannins from Eucalyptus camaldulensis and their potential use in the food industry - Eliseo Sánchez-Loredo; Leonardo Sepúlveda; Jorge E. Wong-Paz; Lissethe Palomo-Ligas; Raúl Rodriguez-Herrera; Cristóbal N. Aguilar; Juan A. Ascacio-Valdés (Exploration of Foods and Foodomics)
Plants play a key role in the treatment and prevention of diseases since ancient times. Eucalyptus has been traditionally used in the treatment of conditions related to the respiratory system, such as flu, colds, sore throats, bronchitis, as well as neuralgia, and stiffness. Eucalyptus camaldulensis has several phytoconstituents such as ellagitannins endowed with bioactivity, including antioxidant and inhibitory potential on various microorganisms causing foodborne diseases. Tellimagrandin I, pedunculagin, castalagin/vescalagin are among the most representative and have activity against pathogens such as Staphylococcus aureus, Escherichia coli, Listeria monocytogenes, and Bacillus cereus. These antioxidant ellagitannins may have potential application in the food, pharmaceutical, and cosmetic industries. The main industrial uses of E. camaldulensis are related to the production of wood, paper, and charcoal, with its leaves and branches considered by-products from these industrial activities. However, these plant by-products could be used to obtain bioactive compounds for the development of new and improved consumer goods. Therefore, the aim of this work was to review the main ellagitannins of E. camaldulensis and their antioxidant and antibacterial activities in foodborne microorganisms, as well as the relevance that these compounds may have in the food industry and related sectors.